A biblical and historical study of homosexuality - Woggon, Harry A. (Journal of religion and health, 1981)
This study is a synthesis of biblical and historical material regarding the place of homosexuality in the Christian churches. The author argues that all sexual activity, both heterosexual and homosexual in orientation, should be judged appropriate for Christians when it is a responsible, mutually respectful and loving act between adult persons that is intended to enhance the building and maintaining of whole persons. Therefore, if a person is in all other ways qualified for membership and its contingent responsibilities in the Christian community (or any other community), his or her sexual orientation and behavior should not be a barrier.